Penguatan Potensi Produk Unggulan Desa melalui Strategi Marketing Syariah berbasis Digital di Desa Rombia Kabupaten Sumenep - A’rasy Fahrullah; Tony Seno Aji; Prayudi Setiawan Prabowo; Ahmad Ajib Ridlwan (Inspirasi Nusantara, 2022)
This Community Service is based on the needs and desires of the villagers of East Rombia Village and West Rombia Village, Kec. Ganding Kab. Sumenep to develop the potential of superior village products. West Rombiya manages the potential that exists in the village, one of which is the management of bananas which are processed into chips. Meanwhile, East Rombia village produces various souvenirs from bags, cups, titles, key chains, to frames. All the souvenirs are made of coconut shells. The village's superior products are still managed in a simple manner as well as the marketing strategy. This PKM aims to provide knowledge to the public regarding marketing strategies. Sumenep is a city of students, where most of the population are Muslims, so the potential for halal tourism or sharia tourism has enormous opportunities. The existence of tourism is a market opportunity for SMEs to market their products. This PKM is trying to implement a sharia-based marketing strategy. Where the solution offered is assistance in making an information system that is used as a marketing tool. This program will make it easier for villages to market their superior products. The application of marketing used is website-based, social media, where with certain branding strategies and marketing by sharia, it is expected to develop superior village products.